2017
DOI: 10.1097/01.nep.0000000000000138
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Content Utilizing a Flipped Classroom Approach

Abstract: The flipped classroom experience promotes retention and accountability for learning. The authors report their evaluation of a flipped classroom for accelerated second-degree nursing students during their primary medical-surgical nursing course. Standardized HESI® scores were compared between a group of students who experienced the flipped classroom and a previous group who had traditional teaching methods. Short- and long-term retention was measured using standardized exams 3 months and 12 months following the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 3 publications
0
42
0
1
Order By: Relevance
“…Some benefits cited have included a higher‐level of learning and further engagement in the material (Bergmann and Sams, ; Marcey and Brint, ; Jeavons et al, ); increase in creativity and critical thinking (Al‐Zahrani, ); a switch to a student‐centered learning environment (Bergmann and Sams, ; Pierce and Fox, ; McLaughlin et al, ); higher‐level of student‐teacher interaction (Bergmann and Sams, ); a more structured approach to learning (Baepler et al, ); and frequently reported increase in student performance (Moravec et al, ; Deslauriers et al, ; Missildine et al, ; Schultz et al, ; Ryan and Reid, ; Cheng et al, ). Quantitative and qualitative studies have been conducted in a variety of STEM courses including general chemistry (Ryan and Reid, ), physiology (Tune et al, ), physics (Deslauriers et al, ), biology (Moravec et al, ), engineering (Rais‐Rohani and Walters, ), and to a smaller extent in the health professions curricula such as nursing (Missildine et al, ; Shatto et al, ), pharmacy (McLaughlin et al, ; Taglieri et al, ), medicine (Tolks et al, ; Zgheib et al, ; Chen et al, ), and physical therapy (Boucher et al, ). However, very few rigorous studies have been conducted in physical therapy curriculum or in upper‐level anatomy courses.…”
Section: Introductionmentioning
confidence: 99%
“…Some benefits cited have included a higher‐level of learning and further engagement in the material (Bergmann and Sams, ; Marcey and Brint, ; Jeavons et al, ); increase in creativity and critical thinking (Al‐Zahrani, ); a switch to a student‐centered learning environment (Bergmann and Sams, ; Pierce and Fox, ; McLaughlin et al, ); higher‐level of student‐teacher interaction (Bergmann and Sams, ); a more structured approach to learning (Baepler et al, ); and frequently reported increase in student performance (Moravec et al, ; Deslauriers et al, ; Missildine et al, ; Schultz et al, ; Ryan and Reid, ; Cheng et al, ). Quantitative and qualitative studies have been conducted in a variety of STEM courses including general chemistry (Ryan and Reid, ), physiology (Tune et al, ), physics (Deslauriers et al, ), biology (Moravec et al, ), engineering (Rais‐Rohani and Walters, ), and to a smaller extent in the health professions curricula such as nursing (Missildine et al, ; Shatto et al, ), pharmacy (McLaughlin et al, ; Taglieri et al, ), medicine (Tolks et al, ; Zgheib et al, ; Chen et al, ), and physical therapy (Boucher et al, ). However, very few rigorous studies have been conducted in physical therapy curriculum or in upper‐level anatomy courses.…”
Section: Introductionmentioning
confidence: 99%
“…Research findings on the impact of flipped-classes on students' learning has also been mixed. There have been some research studies that found flipped-classes have a positive impact on students' learning due to the requirement of needing to be prepared before class (Brunsell & Horejsi, 2013;Enfield, 2013, Van Sickle, 2016, the ability to watch and re-watch out-of-class videos (Sahin, Cavlazoglu, & Zeytencu, 2015), and an increase in students' long term retention (Shatto, L'Ecuyer, & Quinn, 2017;Winquist & Carlson , 2014). However, other research studies have shown no impact on student learning (Adams & Dove, 2016;Baepler, Walker, Driessen, 2014;Jensen, Kummer, & Godoy, 2015;Lape, et al, 2014;Mooring et al, 2016).…”
Section: Flipped-class Design Impact On Students' Learningmentioning
confidence: 99%
“…Recent trends in the basic sciences curriculum in medical education are focused on searching for novel instructional methods to foster application of medical science knowledge. This aim is to stimulate critical thinking and facilitate long-term retention of knowledge [1][2][3][4] . Medical knowledge is growing at a rapid pace, challenging medical educators in selecting which topics to cover and in determining the appropriate breadth and depth of knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, faculty must select the most effective content delivery method to utilize contact time most efficiently [5,6] . It is well documented that the learning process is significantly enhanced when students are motivated and actively engaged in the learning process [4,[7][8][9][10] . Many medical schools have capitalized on these processes and have implemented innovative pedagogical approaches (problem-based learning, team-based learning, etc.)…”
Section: Introductionmentioning
confidence: 99%